PENGGUNAAN MEDIA VISUAL PIRAMIDA MAKANAN SEBAGAI PENGENALAN EKOSISTEM MAKHLUK HIDUP DI KELAS V SD MRAWAN 03 - Fawaid, Alfian Nor; Prayogo, Quwignyo; Mabrur Ridho, Moch Luvdi (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to describe the use of visual media in the form of a food pyramid as a means of introducing the concept of living organism ecosystems to fifth-grade students at SD Mrawan 03. The research employed a qualitative descriptive approach, focusing on students’ understanding and learning experiences during science lessons involving visual media. The subjects consisted of the classroom teacher and 28 fifth-grade students. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing.The findings indicate that the use of visual food pyramid media helps students comprehend the relationships among living organisms within an ecosystem, particularly regarding food chains and environmental balance. This medium provides a more concrete learning experience, allowing students to visually observe the connections between producers, consumers, and decomposers. Furthermore, the teacher reported that the media facilitated material delivery and increased student participation during class discussions. Students became more enthusiastic and were able to explain ecosystem concepts in their own words. Therefore, the visual food pyramid is effective as an alternative instructional medium for science learning that promotes contextual, interactive, and enjoyable learning experiences for elementary school students.